Influence of a Selenium Biofortification on Antioxidant Properties and Phenolic Compounds of Apples (Malus domestica) - Sabrina Groth; Christoph Budke; Susanne Neugart; Sofia Ackermann; Fenja-Sarah Kappenstein; Diemo Daum; Sascha Rohn (MDPI AG, 2020)
Biofortified apples seem to be a suitable produce. In this study, different selenium forms and application levels were applied to the two apple varieties ‘Golden Delicious’ and ‘Jonagold’, grown in the years 2017 and 2018 in order to increase the selenium uptake within a typical Western diet. It was shown that the biofortification, which was performed as a foliar application implemented in usual calcium fertilization, led to significantly increased selenium contents in the fruits. Furthermore, biofortification affected the total phenolic content (TPC), the polyphenol oxidase activity (PPO), as well as the antioxidant activity (AOA), the latter measured with the two well-known assays Trolox Equivalent Antioxidant Capacity Assay (TEAC) and Oxygen Radical Absorbance Capacity Assays (ORAC). The varying selenium forms and application levels showed a differing influence on the parameters mentioned before. Higher fertilizer levels resulted in higher selenium accumulation. It was found that PPO activity fluctuates less in biofortified apples. With regard to TPC, selenate led to higher amounts when compared to the untreated controls and selenite resulted in lower TPC. AOA analysis showed no clear tendencies as a result of the selenium biofortification. In the case of ‘Jonagold’, a higher AOA was generally measured when being biofortified, whereas, in the case of ‘Golden Delicious’, only one form of application led to higher AOA. Additionally, differences in the amount of major phenolic compounds, measured with High Performance Liquid Chromatography Mass Spectrometry (HPLC-DAD-ESI-MSn), were observed, depending on the conditions of the biofortification and the variety.